The ten best practices for test case prioritization - Çatal, Çağatay (Springer-Verlag Berlin, Heidelberger Platz 3, D-14197 Berlin, Germany, 2012)
In this study, test case prioritization approaches that are used to execute the regression testing in a cost-effective manner were investigated. We discussed the critical issues and best practices that a software company should focus on before and after the implementation of test case prioritization techniques inside the company. Due to the increasing complexity of today's software intensive systems, the number of test cases in a software development project increases for an effective validation & verification process and the time allocated to execute the regression tests decreases because of the marketing pressures. For this reason, it is very crucial to plan and setup test case prioritization infrastructures properly in software companies to improve the software testing process. Ten best practices for a successful test case prioritization are introduced and explained in this study.
Keywords: Software Testing; Regression Tests; Test Case Prioritization; Process Improvement; Yazılım Testi; Regresyon Testleri; Test Durumunun Önceliklendirilmesi; Süreç Geliştirme